Cell therapy in patients with left ventricular dysfunction due to myocardial infarction - Panovsky, Roman; Meluzin, Jaroslav; Janousek, Stanislav; Mayer, Jirí; Kaminek, Milan; Groch, Ladislav; Prasek, Jirí; Stanicek, Jaroslav; Dusek, Ladislav; Hlinomaz, Ota; Kala, Petr; Klabusay, Martin; et al. (Echocardiography (Mount Kisco, N.Y.), 2008)
OBJECTIVES: The purpose of this study was to determine the impact of autologous transplantation of mononuclear bone marrow cells on myocardial function in patients with left ventricular (LV) dysfunction due to an acute myocardial infarction. METHODS: The randomized study included 82 patients with a first acute myocardial infarction treated with a stent implantation. This presentation is a subanalysis of 47 patients with left ventricular dysfunction-EF (ejection fraction) <or= 40%. Group H patients (n = 17) received higher number (100,000,000) of cells; Group L patients (n = 13) received lower number (10,000,000) of cells. The patients of control Group C (n = 17) were not treated with cells. The Doppler tissue imaging and single photon emission computed tomography were performed before cell transplantation and 3 months later. RESULTS: At 3 months of follow-up, the baseline EF of 35%, 36%, 35% in Groups H, L, and C increased by 6% (P < 0.01 vs. baseline), 5% (P < 0.01 vs. baseline), and 4% (P = NS vs. baseline), respectively, as assessed by single photon emission computed tomography (P = NS between groups). The baseline number of akinetic segments of 6.9, 7.0, and 6.2 in H, L, and C groups decreased by 1.7 (P < 0.01 vs. baseline), 1.5 (P < 0.01 vs. baseline), and 0.7 (P = NS vs. baseline, P = NS between groups), respectively, as demonstrated by echocardiography. CONCLUSION: In our study, the statistically important effect of transplantation of mononuclear bone marrow cells on myocardial function was not found. Only an insignificant trend toward the improvement of global LV EF fraction was found at 3-month follow-up.
Keywords: výsledek terapie; transplantace kostní dřeně; infarkt myokardu; Bone Marrow Transplantation; dysfunkce levé srdeční komory; Treatment Outcome; Ultrasonography; Male; lidé; Female; mužské pohlaví; ženské pohlaví; Ventricular Dysfunction, Left; lidé středního věku; Humans; ultrasonografie; Middle Aged; Myocardial Infarction